191k views
5 votes
Not sure need help ​

Not sure need help ​-example-1
User AJC
by
6.3k points

2 Answers

6 votes
6(7-2x)=6
•first distribute
6*7=42 6*2x=12x
•then subtract 42 from both sides and cancel out 42
42-12x=6
-42 -42
•then divide -12 from both sides and cancel -12 leaving x
-12x=-36
-12x/-12=-36/-12
x=3
User Amin Arghavani
by
6.2k points
2 votes

Answer:

X = 3

Explanation:

So do 7-2 which equals 5. 5 times 6 because 6 is outside of the parentheses with no symbol, so that means to multiply. That would equal 30. You want your answer to equal 6, so you would want the number inside of the parentheses to be 1, so that 1 times 6 would be 6. 2 x 3 would be sixe, and then 7-6 would equal one. 1 times 6 would be 6. So there is your answer.

User Pureth
by
5.6k points